STRATEGI KEPOLISIAN NEGARA REPUBLIK INDONESIA DALAM MENGUNGKAPKAN PEREDARAN NARKOTIKA DI KABUPATEN SINTANG - NIM. A1011211105, RANGA ARNANTA PRATAMA (Fakultas Hukum Universitas Tanjungpura, 2025)
Abstract This thesis discusses the strategy of the National Police of the Republic of Indonesia in revealing the circulation of narcotics in Sintang Regency. What is the strategy of the National Police of the Republic of Indonesia in uncovering narcotics circulation in Sintang Regency. The purpose of this study is to obtain data and information related to narcotics trafficking cases in Sintang Regency To find out the forms of strategies of the Indonesian National Police in disclosing narcotics trafficking, especially in Sintang Regency. To find out the causal factors and obstacles in the process of implementing the strategy of the Indonesian National Police and its countermeasures. From the results of the research, the strategy of the Sintang Police in uncovering narcotics crimes is carried out using several strategies, including using trapping/covert operations/intelligence techniques or known as entrapment, in uncovering narcotics crimes using 2 (two) trapping techniques, namely covert purchases and informants. Based on the Decree of the National Police Chief Number SKep/1205/IX/2000 concerning the revision of the Juklak and Juknis associations, the criminal investigation process regulates covert purchases. Article 75 J of the Narcotics Law Number 35 of 2009 regulates covert purchase techniques. In addition to using the Covert Purchase Technique, the Sintang Police also uses informants/cepu in uncovering narcotics trafficking crimes, these informants are members of the public who provide information to the police regarding narcotics crime activities. Keywords: strategy; police; narcotics Abstrak Skripsi Ini Membahas Strategi Kepolisian Negara Republik Indonesia Dalam Mengungkapkan Peredaran Narkotika Di Kabupaten Sintang. Bagaimana Strategi Kepolisian Negara Republik Indonesia Dalam Mengungkap Peredaran Narkotika Di Kabupaten Sintang. Adapun tujuan dari penelitian ini Untuk mendapatkan data dan informasi terkait kasus peredaran narkotika di kabupaten sintang Untuk mengetahui bentuk-bentuk strategi Kepolisian Republik Indonesia dalam mengungkapkan peredaran narkotika khususnya di Kabupaten Sintang. Untuk mengetahui faktor penyebab dan hambatan dalam proses penerapan strategi Kepolisian Republik Indonesia dan Upaya penanggulangannya. Dari hasil penelitian strategi kepolisian Polres Sintang dalam mengungkap kejahatan narkotika yang dilakukan dengan menggunakan beberapa strategi antara lain menggunakan teknik penjebakan/operasi rahasia/intelijen atau yang dikenal dengan entrapment, dalam mengungkap kejahatan narkotika menggunakan 2 (dua) Teknik penjebakan yaitu pembelian terselubung dan informan. Berdasarkan Surat Keputusan Kapolri Nomor SKep/1205/IX/ 2000 tentang revisi himpunan Juklak dan Juknis proses penyidikan tindak pidana mengatur mengenai pembelian terselubung. Pasal 75 J Undang-Undang Narkotika Nomor 35 Tahun 2009 mengatur Teknik pembelian terselubung. Selain menggunakan Teknik Pembelian Terselubung Polres Sintang juga menggunakan informan/cepu dalam mengungkap kejahatan peredaran narkotika, informan ini merupakan masyarakat yang memberikan informasi kepada pihak kepolisian terkait kegiatan kejahatan narkotika. Kata Kunci: strategi; polisi; narkotika